HIV infection among child population of the Republic of Bashkortostan - A. B. Latypov; D. A. Valishin (Детские инфекции (Москва))
The aim of the study: to assess the incidence, prevalence, structure by sex and transmission routes of HIV infection among the child population of the Republic of Bashkortostan.A study of data on HIV infection among children 0—17 years in the republic for 2014—2018 was conducted.Results: the average incidence of HIV infection for 2014—2018 in the age group 0—14 years was 3.4 ± 0.4, 15—17 years — 8.7 ± 1.1, 0—17 years — 4.1 ± 0.4 per 100,000 child population of the corresponding age, the average prevalence of HIV infection at the age of 0—14 years — 26.6 ± 1.1, 15—17 years — 17.2 ± 3.1, 0—17 years — 25.2 ± 1.3 per 100,000 child population of the corresponding age. In 2018 compared to 2014 the incidence of HIV infection in the age group 0—14 years increased by 35.3%, 15—17 years — by 45.0%, 0—17 years — by 36.8%, the prevalence — in the age group 0—14 years increased by 27.4%, 15—17 years — 2.6 times, 0—17 years — by 38.3%. In 96.8% of HIV infections in children aged 0—14 years occurred as a result of perinatal transmission of the virus. Among children 0—14 years of age, 55.8% of cases were diagnosed with HIV infection at the age of 0—1 years. In 29.4% of children 0—14 years with perinatal transmission of HIV infection, the disease was detected at the age of 2 years and older. At the age of 15—17 years, sexual transmission of HIV infection prevailed — 90.9%, female adolescents accounted for 78.2%. In 21.8% of cases, HIV infection was detected in adolescents of the female sex during pregnancy follow-up, in 9.1% in the examination in connection with the consumption of drugs.